Socialization of the Implementation of the Halal Product Assurance Law in Pucangan Village, Kartasura Sukoharjo - Yazid, Afthon; Rosidah, Zaidah Nur; Masjupri; Umi Rohmah (Fakultas Ekonomi dan Bisnis Islam - IAIN Lhokseumawe, 2024)
This study delves into social service initiatives in Pucangan Village, Kartasura, focused on educating the public about obtaining halal certificates and the significance of consuming halal products. Led by the Department of Sharia Economic Law (HES) at Raden Mas Said State Islamic University Surakarta, activities encompassed lectures, interactive discussions, evaluations, and result reporting. The primary aim was to familiarize the community with the Halal Product Assurance Law (UU JPH), fostering dialogue between residents and experts to exchange information, address concerns, and clarify ambiguities at the grassroots level. Furthermore, this initiative significantly contributed to the academic advancement and strategic objectives of UIN Raden Mas Said Surakarta, while advancing the field of Sharia economic law in Indonesia. Findings demonstrate that the community service program effectively heightened local awareness of the halal certification process and emphasized the importance of consuming certified products. By assisting small and medium-sized entrepreneurs in navigating certification procedures more efficiently, the program has enhanced food quality standards in the area. Overall, these results underscore the program's success in closing knowledge gaps and promoting adherence to halal standards within the community.